Wrinkling prediction in deep drawing metal forming : kinematic hardening model versus mixed hardening model - Wan Iryana, Wan Md Nor (2017)
One of the common major defects in deep drawing sheet metal forming is wrinkling. It is known as the formation of uneven height at the top rim of a drawn part due to multi-axial stresses acted on the blank material during the deformation process. Although a finite element method has been used to predict this wrinkling defects and has gained acceptance in the industry, the simulations are far from accurately representing the actual forming process. Hence, the objective of this study is to examine the capability of kinematic hardening model and mixed hardening model (kinematic hardening model combines with isotropic hardening model) using Abaqus software version 6.13.1 in predicting wrinkling defects of deep drawing process. The simulation results are validated by comparing with the experimental results. The experimental work consists of two stages: deep drawing experiment and quantifying wrinkling pattern by using coordinate measurement machine. The deep drawing experiment was conducted to produce stainless steel and mild steel square cup using punch and die that were specially designed and fabricated. Initial investigation of the results by using visual inspection on the drawn square cups found that there is similarity in the wrinkling patterns produced by the simulation and deep drawing experiments. To justify this finding and to get better analysis, coordinate measurement machine is used to measure data of wrinkling patterns along specific paths of the experimental deep drawn products. This experimental data are compared to the wrinkling data acquired from simulation results by plotting both data to be represented in the form of graph. It was found that the experimental wrinkling pattern shows in the graph seem to be similar to wrinkling patterns predicted by the kinematic and mixed hardening model. The kinematic hardening model seems to provide a good solution to predict the wrinkling defects. However, the application of mixed hardening model gives better prediction accuracy. The per cent difference of the wrinkling data from these two hardening models versus experimental data are in the range of 11 per cent to 33 per cent for various bending zones of the deep drawing product. It can be concluded this mixed hardening model is more capable to predict wrinkling defects in deep drawing process.